Dual-Hop System Analysis in Nakagami-m Environment - Cvetkovic, A. D.; Stefanovic, M. C.; Sekulovic, N. M.; Mekic, E. S.; Manic, D. (Elektronika ir Elektrotechnika, 2011)
In this paper, performance analysis of dual-hop transmission system is presented. The source-relay (S-R) and relay-destination (RD) channels experience Nakagami-m fading. The generalized case in which desired signal and cochannel interference (CCI) experience mutually different amount of fading is considered. Furthermore, analysis includes the case in which fading severity in S-R and R-D links can be unequal which is real scenario in practice. Outage probability, as an important performance measure, is considered. As an illustration of mathematical formalism, numerical results are presented to show the effects of system and channel parameters on overall performance. Ill. 5, bibl. 5 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.143